Application of information technologies for the optimization of itinerary when delivering cargo by automobile transport - Prokudin, Georgii; Chupaylenko Оlexiy; Dudnik, Olexiy; Prokudin, Oleksii; Dudnik, Alena; Svatko, Vitaliy (Eastern-European Journal of Enterprise Technologies, 2018)
We have proven the applicability of modern tools of information technologies to solve a traveling salesman problem using a combinatorial method and a transport problem, which is stated in the form of a road transport network, by the simplex method. The obtained results of solving these problems were employed when making up the optimum itinerary of cargo delivery along international routes. The methods proposed could solve transportation problems of any dimensionality, both balanced and non-balanced in terms of cargo transportation volumes. Advantageous geographical position of Ukraine and the existence of strong transportation infrastructure is an important basis to form robust economy of Ukraine. The potential of Ukraine in the international market of transportation services is estimated rather high by experts. Based on the Logistics Performance Index, calculated by the World Bank, Ukraine ranks 61, which is the best indicator among all CIS countries. Development of optimal itinerary of cargo delivery along international routes is predetermined by several factors, the main among them being the high cost of transportation services and tough competition between domestic and foreign freight carriers. The application of information technologies in transportation services opens up new prospects for improving the efficiency of freight transportation. Optimization of cargo delivery schemes is one of the key tasks of transport logistics. Combined use of the described methods for solving open network transportation problems, specifically a method of finding the shortest routes in a road transport network and methods for reducing the unbalanced cargo transportation to the balanced form, makes it possible to obtain considerable synergistical, economical, and organizational-technological effects.